Lei logográfica, princípio da abstração e outras heresias: um estudo sobre o método de Leo Strauss de leitura dos diálogos de Platão - Rodrigues, Tiago Azambuja (2025)
This thesis examines Leo Strauss’s method of interpreting Plato’s dialogues, with particular emphasis on his theory of esoteric writing. The study explores the internal coherence and epistemological viability of Strauss’s hermeneutics by analyzing his core interpretive principles – irony, abstraction, and the logographic law – in light of the literary and dialogical structures of the Platonic corpus. Drawing from literary theory, dialogism, and epistemological contextualism, the thesis assesses whether esotericism offers a plausible framework for understanding the complex dynamics of Plato’s texts. Partially inspired by a deconstructionist approach, especially in the distinction between textual, dramatic, and thematic levels (following Henry Berger Jr.), the thesis extends this model to a systematic critique of esoteric interpretation. Through close readings of the Republic and Phaedrus, it challenges the Straussian claim that Plato wrote between the lines, arguing instead that the supposed absences or silences – particularly the abstraction of eros – are better understood as expressions of dramatic tension and philosophical experimentation. As an alternative to the esoteric hermeneutic, the study leaves open the path for a fruitful and original poeticdialogical interpretation of Plato, grounded in conventional literary theory, with emphasis on dialogism and mythopoetic-archetypal theory (notably Mikhail Bakhtin and Northrop Frye) – the latter offering a promising yet unexplored approach to Plato’s dialogues. Far from approaching Strauss’s reading of the dialogues through the prejudice and controversy it evokes, the thesis reinterprets it as a monographic method – productive when applied to specific dialogues, but not universally prescriptive. This shift allows for the preservation of valuable insights from Strauss – such as attention to dramatic form, narrative discontinuities, and ironic complexity – without endorsing the controversial thesis of esoteric doctrine. It concludes that the complexity of the dialogues does not require the hypothesis of hidden doctrines but rather invites interpretive openness – as in the case of the Republic, which is shaped by desire’s sublimation and poetic abstraction, without resorting to the notion of delibera te concealment.